Vocational vehicles and applications - Hilgers, Michael; Achenbach, Wilfried (Springer, 2021)
The aim of this work, consisting of 9 individual, self-contained booklets, is to describe commercial vehicle technology in a way that is clear, concise and illustrative. Compact and easy to understand, it provides an overview of the technology that goes into modern commercial vehicles. Starting from the customer's fundamental requirements, the characteristics and systems that define the design of the vehicles are presented knowledgeably in a series of articles, each of which can be read and studied on their own. This volume, Vocational Vehicles and Applications, discusses the bodies and trailers that are added to a commercial vehicle to make it fit for purpose. Bodies, trailers and specific equipment packages are explained. It offers an excellent overview for readers who are undergoing training and those who are working in the field. Content Vocational vehicles and applications.- Purpose-specific vehicle preparation by the vehicle manufacturer.- Bodies.- Trailers and semitrailers.- Equipment for typical truck functional sectors.- Abbreviations and symbols. The target groups Participants in master classes and those studying individual aspects of commercial vehicle technology Professors and lecturers instructing in the field of commercial vehicle technology Consultants and experts who need background knowledge and technical expertise regarding commercial vehicle technology Personnel working in the commercial vehicle technology or supply industry who are assigned to a new work area Cost planners and logistics companies The Authors Dr. Michael Hilgers is currently director of the testing center at BFDA, a Foton Daimler truck joint venture in China. Before that he was head of different development departments in Commercial Vehicle Development at Mercedes-Benz Trucks. Dr. Wilfried Achenbach has worked in the automotive industry for over 30 years. Recently he retired as Head of Development at Daimler Trucks North America.